The judges and the reparation of «damage to the project of life» - Fernández Sessarego, Carlos (2007)
The author offers a panoramic point of view of the contemporary state of the Law of Damages in general, and of the physical damages according to the contributions of the Philosophy of the Existence, that meant the transcendental change of the vision of the patrimony by another centered in the integral protection of the human being freedom. As a result of it, the author aims his attention in the description, characteristics, jurisprudential reception and suitable repair of the damage to the «project of life»; without forgetting the urgent necessity of an adapting as well as exact formation of the judge in this matter.